Clinical implementation of plasma cell-free circulating tumor DNA quantification by digital droplet PCR for the monitoring of Ewing sarcoma in children and adolescents - Markus G. Seidel; Karl Kashofer; Karl Kashofer; Tina Moser; Tina Moser; Andrea Thueringer; Bernadette Liegl-Atzwanger; Andreas Leithner; Joanna Szkandera; Martin Benesch; Amin El-Heliebi; Amin El-Heliebi; et al. (Frontiers Media S.A., 2022)
BackgroundTreatment stratification and response assessment in pediatric sarcomas has relied on imaging studies and surgical/histopathological evidence of vital tumor cells. Such studies and evidence collection processes often involve radiation and/or general anesthesia in children. Cell-free circulating tumor DNA (ctDNA) detection in blood plasma is one available method of so-called liquid biopsies that has been shown to correlate qualitatively and quantitatively with the existence of vital tumor cells in the body. Our clinical observational study focused on the utility and feasibility of ctDNA detection in pediatric Ewing sarcoma (EWS) as a marker of minimal residual disease (MRD).Patients and methodsWe performed whole genome sequencing (WGS) to identify the exact breakpoints in tumors known to carry the EWS-FLI1 fusion gene. Patient-specific fusion breakpoints were tracked in peripheral blood plasma using digital droplet PCR (ddPCR) before, during, and after therapy in six children and young adults with EWS. Presence and levels of fusion breakpoints were correlated with clinical disease courses.ResultsWe show that the detection of ctDNA in the peripheral blood of EWS patients (i) is feasible in the clinical routine and (ii) allows for the longitudinal real-time monitoring of MRD activity in children and young adults. Although changing ctDNA levels correlated well with clinical outcome within patients, between patients, a high variability was observed (inter-individually).ConclusionctDNA detection by ddPCR is a highly sensitive, specific, feasible, and highly accurate method that can be applied in EWS for follow-up assessments as an additional surrogate parameter for clinical MRD monitoring and, potentially, also for treatment stratification in the near future.